THE LEADERSHIP ROLE OF THE SCHOOL PRINCIPAL IN REALIZING THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT - Agustinawati, Leni; Permana, Johar; Rahyasih, Yayah (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
This study aims to obtain information on the implementation and influence of the 5-character education interest program on improving the character of students in elementary schools, which is carried out in Purwakarta District. This research took data using a qualitative approach with descriptive methods. The techniques used were observation, interview, and literature study as data collection techniques. This research was conducted in seven schools, representing each cluster in the Purwakarta sub-district. The results of this study obtained information about the cultivation of character values from the 5 Flower Character Program implemented in elementary schools in Purwakarta sub-district, which has been implemented and instilled character values in students through several different activities every day. This research has the implication that the implementation of the Five Flower Character Education Program in schools can instill character values in students to improve their ability and quality at school and outside of school. The purpose of this study is to examine the principal's leadership role in implementing the Student Profile Strengthening Project (P5) at SMP 10 Purwakarta. This study examines the tactics and efforts used by the principal to implement P5 in the classroom setting using a qualitative research methodology. P5 implementation in a classroom setting. In-depth interviews with administrators, educators, and students were used to gather data, and participant observation during P5 activities was also used. Active observation while engaging in P5 tasks. The findings demonstrated that the principal is crucial in fostering stakeholder cooperation, socializing P5's vision and goal, and establishing a learning environment that fosters the growth of Pancasila values. a setting for learning that fosters Pancasila values growth. Transformative and participatory leadership styles are used to enable every student in the school to execute P5. Educating the school community about P5. Furthermore, the principal initiation changes to the curriculum and included Pancasila values into the educational process. This study adds to our knowledge of the principal's leadership responsibilities in promoting character education initiatives in schools. The results can serve as a guide for other educational institutions seeking to improve students' identity and character as Pancasila citizens of Indonesia by implementing P5 or programs akin to it.